1999
DOI: 10.1128/jvi.73.2.1127-1137.1999
|View full text |Cite
|
Sign up to set email alerts
|

Bovine Leukemia Virus-Induced Persistent Lymphocytosis in Cattle Does Not Correlate with Increased Ex Vivo Survival of B Lymphocytes

Abstract: Bovine leukemia virus (BLV) is an oncogenic retrovirus associated with B-cell lymphocytosis, leukemia, and lymphosarcoma in the ovine and bovine species. We have recently reported that in sheep, BLV protects the total population of peripheral blood mononuclear cells (PBMCs) from ex vivo spontaneous apoptosis. This global decrease in the apoptosis rates resulted from both direct and indirect mechanisms which allow extension of cell survival. Although sheep are not natural hosts for BLV, these animals are prone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 28 publications
1
7
1
Order By: Relevance
“…Remarkably, these findings disagree with several reports that did not notice any changes in the B‐cell population of PL − animals (Gatei et al, 1989; Levkut et al, 1995; Dequiedt et al, 1999). To our knowledge, no reports exist describing a statistically significant reduction in B cells only.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Remarkably, these findings disagree with several reports that did not notice any changes in the B‐cell population of PL − animals (Gatei et al, 1989; Levkut et al, 1995; Dequiedt et al, 1999). To our knowledge, no reports exist describing a statistically significant reduction in B cells only.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast, contradictory views exist on the distribution of B and T cells in the peripheral blood of BLVinfected cattle which are haematologically inconspicuous. Whereas in several investigations no differences in the percentage and number of B cells have been observed (Gatei et al, 1989;Sordillo et al, 1994;Levkut et al, 1995;Dequiedt et al, 1999;Lundberg and Splitter, 2000), a decrease in these cells has been detected by Meirom et al (1993).…”
Section: Introductionmentioning
confidence: 91%
“…Whether the proliferating B lymphocytes are infected with BLV is not known. In agreement with a previous report (Dequiedt et al , 1999 ) we observed that lymphocytes expressing BLV p24 during unstimulated culture were spared from apoptosis. Our results extend this observation and suggest that the ability of BLV expression to prevent apoptosis may be tied to its ability to arrest or delay cells in G 0 /G 1 of the cell cycle.…”
Section: Discussionsupporting
confidence: 94%
“…Susceptibility to apoptosis associated with BLV infection seems to vary from one species to another. B cells from lymphocytotic sheep appear to be protected from ex vivo spontaneous programmed cell death (Dequiedt et al , 1997 ; Schwartz-Cornil et al , 1997 ), while PBMCs from persistently lymphocytotic BLV-infected cows are more susceptible to ex vivo apoptosis than PBMCs from uninfected or aleukaemic animals (Dequiedt et al , 1999 ). According to our results, primary macrophages from uninfected sheep and cows, infected in vitro with BLV, were similarly resistant to apoptosis.…”
Section: Discussionmentioning
confidence: 99%